ChemInform Abstract: One‐Pot Double Benzylation of 2‐Substituted Pyridines Using Palladium‐Catalyzed Decarboxylative Coupling of sp2 and sp3 Carbons. Issue 16 (April 2015) - Wang, Yaping; Li, Xinjian; Leng, Faqiang; Zhu, Helong; Li, Jingya; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Abstract The title reaction uses a bimetallic catalytic system consisting of PdCl2 and Ag2O.